Analisis Putusan No.39/Pid.B/2015/PN/Sit Dalam Perkara Tindak Pidana Pembalakan Liar Ditinjau Dari Aspek Keadilan - Aristo Arie Notoprojo; Sholahuddin Al-Fatih; Catur WIdo Haruni (Universitas Muhammadiyah Malang, 2022)
The Illegal logging is an organized illegal timber use activity. This crime is usually carried out by more than two people in a certain time for the purpose of destroying forests and selling wood products illegally. In Decision No.39/Pid.B/2015/PN.Sit the defendant Asyiani was dropped by a criminal witness of illegal logging thanks to a special criminal offense. Where the defendant has carried out illegal logging on Perhutani's land. The problem with this research is What is the basis for the judge's consideration in Decision No.39/Pid.B/2015/PN.Sit regarding the crime of illegal logging and How due to the law of Decision No.39/Pid.B/2015/PN.Sit about the crime of illegal logging is reviewed from the justice aspect. The research methods used are normative legal methods that use primary legal materials, secondary legal materials, tertiary legal materials and data analysis. The results of the study show less precisely the judge's consideration in the case against the defendant and the legal consequences reviewed from the aspect of pancasila justice were less appropriate because the defendant was given a probation sentence in which the criminal act of illegal logging was one special crime. The author's advice needs to be done with fair funding according to the crime committed by the defendant and this problem can be resolved by deliberation